1996
DOI: 10.1159/000184830
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Severe Hypoglycaemia in Children with Insulin-Dependent Diabetes Mellitus

Abstract: The literature contains numerous reports of the frequency of severe hypoglycaemia in childhood insulin-dependent diabetes mellitus. Unfortunately, most of these data have been collected in such a manner as to make comparisons between them difficult. Most reports have used small, well-defined populations of children who were participants in larger, complex, clinical studies. Additional difficulties are encountered in the standardization of the definition of severe hypoglycaemia. Some studies have required that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…A higher number of severe hypoglycemic episodes was found in patients with a basal/bolus ratio >0.8 (basal insulin >45% of the total insulin dose). This finding has been reported previously by Clarke et al (15) and may be because of the larger basal insulin (long‐acting analogues) dose, which by lasting longer might lead to hypoglycemia episodes caused by interprandial hyperinsulinemia which impairs hepatic glucose production. In our study, age group trend analysis shows that most severe hypoglycemic episodes occur in subjects aged 7–12 yr.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A higher number of severe hypoglycemic episodes was found in patients with a basal/bolus ratio >0.8 (basal insulin >45% of the total insulin dose). This finding has been reported previously by Clarke et al (15) and may be because of the larger basal insulin (long‐acting analogues) dose, which by lasting longer might lead to hypoglycemia episodes caused by interprandial hyperinsulinemia which impairs hepatic glucose production. In our study, age group trend analysis shows that most severe hypoglycemic episodes occur in subjects aged 7–12 yr.…”
Section: Discussionsupporting
confidence: 78%
“…A large number of studies have evaluated the incidence of SH and predisposing factors in children and adolescents with T1DM, with mixed results (3, 4, 8–19). Indeed, the reported incidence of SH in children and adolescents varies widely from 3.1 episodes per 100 patient‐years to 66 episodes per 100 patient‐years (8, 9).…”
mentioning
confidence: 99%
“…The findings highlight the possibility that these effects may be particularly debilitating and persistent if hypoglycemic episodes begin earlier in development. Children with IDDM are at significant risk for recurrent hypoglycemia (Clarke et al, 1996); moreover, many of their hypoglycemic episodes go undetected (Gonder-Frederick et al, 2008). Indirect but compelling evidence to support this notion was provided by a recent study of paramedic calls for monitoring or treatment of acute hypoglycemia which showed that such calls are less frequent for children 0–9 years of age than for adolescents or young adults (Vilke et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the rate of severe hypoglycemia decreased significantly in both subgroups on FMDI. While the etiology of severe hypoglycemia in type 1 DM is multifactorial and includes reduced awareness of the symptoms of hypoglycemia and overall level of glucose control [33], it is usually associated with self-management errors, vigorous physical activities, psychosocial stresses, 1 or 2 daily injections, and lower proportion of short-acting insulin out of the total daily dose [7]. In our patient population, institution of FMDI treatment resulted in redistribution of insulin dose throughout the day with higher proportion of short-acting insulin out of the total daily dose.…”
Section: Discussionmentioning
confidence: 99%